Current challenges of the batik industry in Malaysia and proposed solutions - Marzuki, Ibrahim; Hartini, Mohd Razali; Mazni, Omar; Siti Fairuz, Md Hashim (2021)
Batik is an art or craft that is produced through a variety of textile designing techniques. In Malaysia, batik is considered as a national heritage art that is the pride of the country. The World-Asia Pacific Craft Council recognizes Malaysian batik as one of the most well-known local crafts globally. This study aims to examine the challenges faced by the batik industry in Malaysia. The literature review method is fully utilized to collect the required data. The results of the study found that the Batik Industry in Malaysia faces the challenge of competition from cheaper and modern external products and even more worrying is the original batik design imitated by irresponsible foreign entrepreneurs by offering lower prices. The lack of skilled workers from young people should also be taken into consideration when many young people voices that they are not interested in working in this industry. A more detailed research study proposal is needed by paying attention to the role of entrepreneurs and designers in the batik industry in Malaysia. They are the leading movers in addressing the challenges and problems that exist in this industry in line with efforts to develop the local batik industry and elevate the art of batik in Malaysia.